Security and Privacy in Communication Networks 7th International ICST Conference, SecureComm 2011, London, UK, September 7-9, 2011, Revised Selected Papers - Rajarajan, Muttukrishnan; Piper, Fred.; Wang, Haining; Kesidis, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume presents the refereed proceedings of the 7th International ICST Conference on Security and Privacy in Communication Networks, SecureComm 2011, held in London, UK, in September 2011. The 35 revised papers included in the volume were carefully reviewed and selected from numerous submissions. Topics covered include network intrusion detection; anonymity and privacy; wireless security; system security; DNS and routing security; and key management.
network intrusion detection -- anonymity and privacy -- wireless security -- system security -- DNS and routing secuity -- key management.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Information Systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Computer Communication Networks; Data Encryption; Information Systems Applications (incl. Internet).; Operating Systems